Proceedings of the Ocean Drilling Program 1991
DOI: 10.2973/odp.proc.sr.114.173.1991
|View full text |Cite
|
Sign up to set email alerts
|

On the Tectonic History and Origin of the Northeast Georgia Rise (Synthesis)

Abstract: Northeast Georgia Rise is located on inferred oceanic crust that is considered Albian in age and to have formed during the separation of Africa and South America. Of the three sites (698, 699, and 700) drilled on the rise during ODP Leg 114, Site 698 reached basement. Basalt overlying a weathered regolith was recovered at Site 698 and a basaltic substratum at the other sites is inferred from the downhole variation in pore-water chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…Thus the arc must have been active by 28.5Ma and was probably active by 32.5Ma. On ODP Leg 114, Kristoffersen and LaBrecque (1991) identified an early Oligocene extensional tectonic event through drilling and seismic imaging of the Northeast Georgia Rise, so providing possible independent evidence of subduction initiation at this time.…”
Section: Subduction Initiation In the Northern Assamentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the arc must have been active by 28.5Ma and was probably active by 32.5Ma. On ODP Leg 114, Kristoffersen and LaBrecque (1991) identified an early Oligocene extensional tectonic event through drilling and seismic imaging of the Northeast Georgia Rise, so providing possible independent evidence of subduction initiation at this time.…”
Section: Subduction Initiation In the Northern Assamentioning
confidence: 99%
“…Dalziel et al (2013) postulated that the collision is between the Northeast Scotia Rise and the South Georgia microcontinent, a possibility that was also discussed by Barker (2001) in a different context. Kristoffersen and LaBrecque (1991) documented the history of this terrane in some detail using seismic reflection profiles together with structural and stratigraphic data from ODP Leg 114, which drilled three sites on the rise. They concluded that the 400x400km terrane formed by 'excessive volcanism' at a Cretaceous ridge crest followed by off-axis volcanic eruptions.…”
Section: Death Of the Northern Assa By Terrane Collisionmentioning
confidence: 99%
“…The exact tectonic evolution has been widely discussed. The latest hypothesis considers the main crustal growth to have been controlled by the proximity of several spreading centres and passage over the Bouvet Hotspot at 80-100 Ma, and thus adds the plateau to the world-wide suite of large igneous provinces (LIP) of predominantly oceanic origin (Labreque and Hayes, 1979;Allen and Tucholke, 1981;Martin and Hartnady, 1986;Kristoffersen and Labreque, 1991;Ben-Avraham et al, 1995;Uenzelmann-Neben et al, 1999;Gohl and Uenzelmann-Neben, 2001). …”
Section: Geological and Oceanographic Setting Of The Agulhas Plateaumentioning
confidence: 99%
“…This hypothesis states that the Agulhas Plateau formed one structural unit together with the Falkland Plateau and Maud Rise prior to the opening of the South Atlantic. ODP drilling at the Northeast Georgia Rise, however, led to the suggestion of an equivalent evolution of the Northeast Georgia Rise and the Agulhas Plateau, and thus an oceanic origin of the Agulhas Plateau (Kristoffersen and LaBrecque, 1991). An attempt to solve the puzzle of the evolution of the plateau by seismic investigations and geological sampling was already made by Barrett (1977), Tucholke and Carpenter (1977), and Allen and …”
Section: Introduction and Data Acquisitionmentioning
confidence: 99%